Molecular Characterization of Mungbean yellow mosaic India virus and Tomato leaf curl New Delhi virus in Sukoharjo and Magelang Regencies, Indonesia - Surwadinata, Antama; Putro, Ananda Restu; Pradhana, Adhi; Shalihah, Filzah; Pancasona, Muhammad Garda; Saputra, Rachmad; Haj Ali, Mayadah A.; Santosa, Adyatma Irawan (Jurnal Perlindungan Tanaman Indonesia, 2025)
Diseases caused by Begomoviruses in black-eyed pea (Vigna unguiculata subsp. unguiculata) and cucumber (Cucumis sativus) are remains insufficiently explored in Indonesia. One symptomatic black-eyed pea and two cucumber samples were collected from Sukoharjo and Magelang Regencies, respectively, to be molecularly tested using Krusty/Homer and SPG1/SPG2 primer pairs for universal detection of Begomoviruses. NCBI BLAST analysis on the obtained nucleotide sequences confirmed mungbean yellow mosaic India virus (MYMIV, Begomovirus vignaradiataindiaense) infection in black-eyed pea sample and tomato leaf curl New Delhi virus (ToLCNDV, Begomovirus solanumdelhiense) infection in both cucumber samples. Sequences of partial AV1, and partial AC1 and AC2 genes of the three isolates were registered with accession nos. PQ539469-71 and PQ539476-78, respectively, in NCBI GenBank. No recombination signal was detected in the sequences of the new isolates according to scan by Recombination Detection Program (RDP v.5.30). In the phylogenetic trees built by MEGA 11 software with Tamura-Nei parameter model, MYMIV H-2 as well as ToLCNDV N-8 and V-97 isolates shared basal nodes with Indonesian isolates, indicated their close genetic relationship with other isolates also found in the country. While expanding our information regarding genetic diversity of Begomoviruses, this study also reported the first cases of MYMIV in black-eyed pea in Indonesia and ToLCNDV in cucumber in Magelang, to the best of our knowledge.